NILAI PANCASILA DALAM SYAIR SINDHENAN GAYA SURAKARTA - Sukesi (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
Pancasila is the foundation of the state that has an important position in the life of Indonesian society. Every aspect of the life of the nation and state ranging from law, politics, economics, to art and culture must always be based on the values of Pancasila. In the aspect of arts and culture, Pancasila values are reflected in various traditional art forms, one of which is in Surakarta-style sindhenan poetry. Research on Pancasila Values in Surakarta Style Sindhenan Poetry is an attempt to explore Pancasila values contained in sindhenan poetry commonly used in Surakarta Style Karawitan repertoire. The purpose of this research is to show that the position of the sindhen is not only an object of sound and visual exploitation, but the ability of the sindhen to convey the values of Pancasila which is the basis of the Indonesian state. Thus, this shows that pesindhen have played an active role in socialising the foundation of the state as a way of life as well as the identity of the Indonesian Nation. The result of this research is the existence of Pancasila values and its points as contained in the 2003 TAP MPR RI in Surakarta style sindhenan poetry, especially in the wangsalan section.